(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2014)
In the family of Euphorbiaceae, the genera Euphorbia and Sapium are known to contain essentially latex-bearing species. In the present study, the latex of Euphorbia selloi (Klotzsch & Garcke) Boiss., Euphorbia papillosa A.St.-Hil., and Sapium glandulosum (L.) Morong, plants native from Brazil, were examined concerning proteolytic activity. All studied species have proteins with significant proteolytic activity and E. papillosa has the greatest specific activity. Aiming to verify the type of protease present, an assay with different inhibitors was performed. In the three tested plants, the proteolytic activity was significantly inhibited by a serine protease inhibitor 4-(2-aminoethyl)-benzenesulfonyl fluoride hydrochloride (AEBSF). Using techniques of electrophoresis with polyacrylamide gels (SDS-PAGE), the subunits of proteins were separated according to their molecular masses, and the protein activity was visually detected by zymography.